Waqf land management for property development: a catalyst for welfare and benefits to the poor / Dr. Zuraidah Mohamed Isa, Dr. Dahlia Ibrahim and Zaiful Affendi Ahmad Zabib - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ahmad Zabib, Zaiful Affendi (Universiti Teknologi MARA, Kedah, 2024)
Waqf, also spelt as wakf or waqaf, is an Islamic law concept that involves the endowment or dedication of a specific asset or property, usually in the form of real estate, for religious, charitable, or philanthropic purposes. The person who creates a waqf is known as a "waqif" or "donor". The properties or assets dedicated to waqf become the waqf's corpus and any income generated from it is used to support the intended charitable or religious cause. As an Islamic philanthropic, waqf holds a unique position in the socio-economic fabric of Muslim societies. Traditionally, waqf has been associated with the dedication of assets, including land, for charitable and welfare purposes; however, the focus has recently shifted towards exploring the economic potential of waqf lands through property development with the aim of generating sustainable revenue streams for the benefit of the underprivileged.